Edukasi Keamanan Siber dan Perlindungan Data Transaksi Digital Bagi Pelaku Usaha Di Ekosistem Marketplace - Kornelius Kornelius; Naimah Naimah; Cahaya Sukma; Lela Budiarti; Alwendi Alwendi (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2026)
The rapid development of the marketplace ecosystem has significantly driven the increase of digital transaction activities among business actors, including micro, small, and medium enterprises. The ease of access, operational efficiency, and broad market reach offered by digital platforms provide substantial opportunities for digital economic growth. However, this increase is also accompanied by rising cybersecurity risks such as phishing, malware, account hacking, and theft or misuse of transaction data. This condition requires systematic efforts to enhance digital security literacy through cybersecurity and data protection education. This study aims to analyze the effectiveness of cybersecurity education in improving understanding, awareness, and data protection practices related to digital transactions among business actors in the marketplace ecosystem. The research method used is a qualitative descriptive approach with data collection techniques through observation and interviews with active marketplace users. The results indicate that cybersecurity education significantly improves the digital literacy of business actors, particularly in recognizing potential threats and applying appropriate mitigation measures. In addition, trained business actors tend to be more disciplined in managing transaction data in a secure and structured manner. Therefore, cybersecurity and data protection education play an important role in strengthening the digital resilience of business actors in the increasingly complex and dynamic digital economy era, as well as supporting sustainable digital transformation in Indonesia. Collaboration between government, platforms, and businesses is essential for improving data security and trust.